2014
DOI: 10.1038/sj.bdj.2014.100
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap! A comparison of oral health knowledge between dental, healthcare professionals and the public

Abstract: The results of this survey demonstrate a knowledge gradient from dental professionals through to healthcare professionals and then to lay members of the community. The knowledge base observed in the dental group is reflected in the other two groups as would be expected albeit with a significant gap between each group. As expected the dental professionals are generally well informed, but not as well informed as could be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…The full text of the remaining 21 papers was retrieved, and six additional reports were excluded for investigating convenience samples 32–37 . Three papers were discarded for focusing on other aspects of periodontology 38–40 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The full text of the remaining 21 papers was retrieved, and six additional reports were excluded for investigating convenience samples 32–37 . Three papers were discarded for focusing on other aspects of periodontology 38–40 .…”
Section: Resultsmentioning
confidence: 99%
“…The full text of the remaining 21 papers was retrieved, and six additional reports were excluded for investigating convenience samples. [32][33][34][35][36][37] Three papers were discarded for focusing on other aspects of periodontology. [38][39][40] An additional set of two reports was precluded for using non-original data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a re‐emphasis on prevention with tooth‐preserving operative intervention only provided as a last resort to more closely align upstream, midstream and downstream efforts at caries control, while seeking to reduce health inequalities globally (Pitts et al , ). The crucial issues going forward include closing the oral health knowledge gradient and transforming health education on caries prevention/control among all healthcare professionals and the public (Richards et al , ). A recent step forward is The ICDAS Foundation's International Caries Classification & Management System (ICCMS ™ ), which has been simplified into an implementation I CCMS ™ Guide for Practitioners and Educators by an international group (Pitts et al , ).…”
Section: Major Oral Diseases and Conditionsmentioning
confidence: 99%
“…Chu et al [11] reported a low level of awareness and knowledge of erosive tooth wear among adults aged 25 to 45 years in Hong Kong. A knowledge gradient regarding erosive tooth wear has been identified, with dental professionals having the most knowledge, followed by healthcare professionals and then laypersons [12]. However, the knowledge level of dental professionals is not as high as expected.…”
Section: Introductionmentioning
confidence: 98%